Limited liability of partnership act: a proposal for Malaysia / Tengku Rinanda Putri Tengku Aziz…[et al.] - Tengku Aziz, Tengku Rinanda Putri; Mohd Awal, Puteri Noorhazatul Ezra; Abd Rahman, Azrina; Kamaruddin, Hanisah (Faculty of Law, 2005)
The purpose of our project paper is to determine the problems that occur in Malaysia's Partnership, which is, governed by the Partnership Act 1961. But the main focus of this project paper is on the liability of the partners in partnership. There are several disadvantages mainly on the liability of partners in Malaysia. The main problem for partners in Malaysia is that their liability is unlimited. For example if any problems occur in a firm, the partners will be held liable personally. Other than that, every partner can be said to be liable jointly and severally for everything that had been done towards the firm while the member is a partner. It can also be said that partners will be liable for the debts of the firm even it is caused by other partners. That is why we would like to propose the Limited Liability of Partnership Act (LLP) in Malaysia to fill the lacuna in the law of partnership, whereby in LLP the liabilities of the partners are limited. As a conclusion, what we had achieved is that majority of the people in the business world do agree that we should adopt the Limited Liability of Partnership Act 2000 in United Kingdom into the Partnership Act 1961 Malaysia.